ANALYZING THE FACTORS INFLUENCING ROAD TRAFFIC ACCIDENT SEVERITY IN BAUCHI STATE - Muhammed Gambo, Ali; A., Abdulkadir; K.E , Lasisi (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Road traffic accidents are a complex global issue due to their impact on both financial and public health sectors. Bauchi State, with approximately 1334 kilometers of roadways, experiences a significant number of accidents. To mitigate accident severity, it is crucial to analyze the factors influencing road traffic accident severity in Bauchi State. This study employs multinomial logistic regression to predict accident severity—fatal, serious, and minor—from 422 accidents recorded between January 2021 and December 2022 by the RTC unit of FRSC. Significant factors identified include accident location, cause, route, vehicle class, presence of at least one female passenger, vehicle type, accident timing, and driver’s gender. The findings of this study and its recommendations will inform the development and implementation of future road safety policies and measures.